A Retrospective Hospital Based Study In Kathmandu to Assess the Seroprevalence of Hepatitis B Virus - Bhatta, Bibek; Thapa, Roshana; Pant, Pankaj; Pandeya, Dipendra Raj (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Background Hepatitis B is a major public health issue in Nepal. Acute as well chronic Hepatitis B infection can lead to different hepatic manifestation ranging from acute liver failure, aplastic anemia and liver cirrhosis to liver cancer. Although, there is a presence of high burden of viral hepatitis in Nepal but little have been studied about it. So this study was aimed to obtain the seroprevalence of Hepatitis B among all the patients: outpatient as well as patient in different wards visiting a tertiary care hospital. Methods This was a retro prospective study conducted at a tertiary care hospital in which the data was obtained from the university register. The data documents the seroprevalence of Hepatitis B. In this study we have assessed total of 240 samples all of which were processed at Microbiology and Pathology laboratory using commercially available kits. Data were cleaned manually and analyzed using SPSS vs. 20. Results Out of 240 samples assed, 158 were males and 82 females and we found a total viral hepatic burden of 4.19% (10 samples).The mean age group of our study was 47 years (9 years to 85 years). Out of HBsAg screened positive population, HBV was seen mostly in males (90%) whereas lesser in female (10%). Conclusions Viral hepatitis usually does not follow any seasonal pattern so emphasis must be given to pre-exposure and post-exposure prophylaxis so that we can prevent people from casualties caused via viral hepatitis. Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.3-6